2023
DOI: 10.1111/nph.19354
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone deficiency induces jasmonate, sugar and flavonoid phytoalexin accumulation enhancing rice defense against the blast fungus Pyricularia oryzae

Zobaida Lahari,
Sarah van Boerdonk,
Olumide Owolabi Omoboye
et al.

Abstract: Summary Strigolactones (SLs) are carotenoid‐derived phytohormones that regulate plant growth and development. While root‐secreted SLs are well‐known to facilitate plant symbiosis with beneficial microbes, the role of SLs in plant interactions with pathogenic microbes remains largely unexplored. Using genetic and biochemical approaches, we demonstrate a negative role of SLs in rice (Oryza sativa) defense against the blast fungus Pyricularia oryzae (syn. Magnaporthe oryzae). We found that SL biosynthesis and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…To quantify naringenin and sakuranetin, the 1260 HPLC‐QTRAP 6500 mass spectrometer system equipped with a turbo‐spray ion source was operated in positive ionization mode, as detailed in Lahari et al. (2024). The concentrations of naringenin and sakuranetin were determined by comparison to D 6 ‐ABA, applying the experimental response factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify naringenin and sakuranetin, the 1260 HPLC‐QTRAP 6500 mass spectrometer system equipped with a turbo‐spray ion source was operated in positive ionization mode, as detailed in Lahari et al. (2024). The concentrations of naringenin and sakuranetin were determined by comparison to D 6 ‐ABA, applying the experimental response factors.…”
Section: Methodsmentioning
confidence: 99%
“…(1998) reported that JA increases the activity of PAL enzymes in tobacco and the accumulation of phenylpropanoids like coumarin and scopoletin. In rice, JA is known to enhance the accumulation of phenylpropanoid pathway‐derived phytoalexins, including naringenin and sakuranetin, enhancing defence against blast fungus (Lahari et al., 2024; Ogawa et al., 2017). On the other hand, an earlier study shows that the activation of the phenylpropanoid pathway leads to a decrease in JA concentration and downstream signalling (Alon et al., 2013), indicating complex relationships between both pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AtD14, MAX2 encoding an F-box protein, and the transcription factors BRC1/2 are involved in the strigolactone signaling pathway in Arabidopsis [ 251 ]. Strigolactones not only participate in stimulating the germination of parasitic plants like striga but also play a crucial role in the symbiosis between plant roots and arbuscular mycorrhizal fungi [ 252 ]. Recent studies have found that root-secreted strigolactones promote plant symbiosis with beneficial microorganisms and participate in the interaction between plants and pathogenic microorganisms.…”
Section: Biosynthesis and Molecular Mechanisms Of Allelochemicals And...mentioning
confidence: 99%
“…For example, SLs play a negative regulatory role in the defense of rice against the rice blast fungus ( pyricaria oryzae ). The reduction in strigolactone levels in rice enhances its defense against the rice blast fungus by activating jasmonic acid and sugar signaling pathways, as well as accumulating flavonoid phytoalexins [ 252 ].…”
Section: Biosynthesis and Molecular Mechanisms Of Allelochemicals And...mentioning
confidence: 99%
“…Studying the relationship between alterations in carbon allocation and resistance to M. oryzae will be crucial to comprehend the molecular processes that underlie plant defense reactions. 25 , 31 , 62 The goal of these investigations is to understand how changes in the carbon distribution of resources affect a plant’s capacity to fend off and defeat the invasive pathogen. Future research should examine how dynamic changes in carbon allocation patterns occur during rice blast infections, with an emphasis on how photosynthetically fixed carbon is redistributed to areas that are being attacked by pathogens.…”
Section: Introductionmentioning
confidence: 99%